PENGARUH KONSELING GIZI TENTANG KONSUMSI DAUN KATUK DAN KACANG HIJAU DENGAN MEDIA BOOKLET TERHADAP PERILAKU IBU MENYUSUI DI KECAMATAN PERCUT SEI TUAN - Ratna Zahara; Lusyana Gloria Doloksaribu; Rohani Retnauli Simanjuntak (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2021)
ABSTRACT Breastmilk (ASI) is the best life fluid that is needed by babies, containing various important substances for the baby's growth and development according to their needs. The success of breastfeeding is influenced by the nutrients consumed by the mother during pregnancy and breastfeeding. This study was conducted to determine the effect of breastfeeding counseling using bookletters on breastfeeding behavior in Percut Sei Tuan District. This type of research is a quasi-experimental (Quasy experiment) with a pre-test research design and a post-test design with a comparison group. Conducted in March - August 2020, the samples were breastfeeding mothers in Percut Sei Tuan District in Cinta Rakyat Village as an intervention group and breastfeeding mothers in Cinta Damai Village as a comparison group. Samples and controls were selected by "purposive sampling" each of 30 samples. The data consisted of primary data and secondary data, processed and univariate analysis was carried out to see the frequency distribution based on knowledge and attitudes in the menu selection of breastfeeding mothers followed by bivariate analysis using the dependent t-test to compare knowledge, attitudes and actions of respondent eating before (pre) and after (post) counseling. From the research conducted, there were differences in the knowledge of mothers from the intervention group and the comparison group, there were differences in attitudes in the two groups, and there were differences in actions in the two groups after counseling using booklet media. Booklet-based counseling influences the mother's actions in breastfeeding her baby. Keywords: breastfeeding, counseling, booklets, breastfeeding behavior